Guideline for feedback of individual genetic research findings for genomics research in Africa. Issue 1 (11th January 2022) - Matimba, Alice; Ali, Stuart; Littler, Katherine; Madden, Ebony; Marshall, Patricia; McCurdy, Sheryl; Nembaware, Victoria; Rodriguez, Laura; Seeley, Janet; Tindana, Paulina; Yakubu, Aminu; de Vries, Jantina
Abstract : As human genomics research in Africa continues to generate large amounts of data, ethical issues arise regarding how actionable genetic information is shared with research participants. The Human Heredity and Health in Africa Consortium (H3Africa) Ethics and Community Engagement Working group acknowledged the need for such guidance, identified key issues and principles relevant to genomics research in Africa and developed a practical guideline for consideration of feeding back individual genetic results of health importance in African research projects. This included a decision flowchart, providing a logical framework to assist in decision-making and planning for human genomics research projects. Although presented in the context of the H3Africa Consortium, we believe the principles described, and the decision flowchart presented here is applicable more broadly in African genomics research.